Elements of business and technical writing - De Belen, Rustico T.; Enriquez, Bernadette B. (Quezon City : Wiseman's Books Trading Inc., 2015)
"Elements of Business and Technical Writing" - is an excellent guide for students of all courses who want to improve their technical writing skills. It has three chapters: (12) Business Correspondence, (2) Tools for the Job Hunt, and (3) Mechanics of Technical Writing. It addresses the need to make business and technical writing ridiculously easy." --Preface
Includes bibliography and references.
Keywords: Technical writing